In vitro effect of the herbicide glyphosate on human blood platelet aggregation and coagulation - Neiva,Teresinha de Jesus C. (2010)
Glyphosate [N-(phosphonomethyl)-glycine] is a broad-spectrum, non-selective, post-emergence herbicide that is extensively used in agriculture. Published data referring to the effects of this product on human health are contradictory. We showed previously that long-term treatment of rats with low doses of Glyphosate-Biocarb® may induce hepatic histological changes and bleeding without decreasing platelet counts. The aim of the current study was to investigate, in vitro, the effect of glyphosate on human blood platelet aggregation and coagulation. Materials and methods: Platelet aggregation was determined in the platelet-rich plasma using the agents: 6µM-adenosine diphosphate, 6µM-epinephrine and 4µg/mL-collagen. Pretreatment with 500µg/mL glyphosate showed significant hypofunction of the three aggregating agents. The inhibitory effect was dose-dependent at concentrations from 50 to 500 µg/mL. The release of ATP was lower for glyphosate-treated platelets after stimulation by collagen. On the other hand, glyphosate did not promote any inhibitory effects on prothrombin time, thromboplastin time and thrombin time. In conclusion, the results demonstrate that glyphosate promotes changes in the platelet metabolism with an inhibitory effect on primary hemostasis.